2011
DOI: 10.3174/ajnr.a2286
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Dilemma of Pseudoprogression in the Treatment of Newly Diagnosed Glioblastomas: The Role of Assessing Relative Cerebral Blood Flow Volume and Oxygen-6-Methylguanine-DNA Methyltransferase Promoter Methylation Status

Abstract: BACKGROUND AND PURPOSE:Methylation of the MGMT gene promoter is associated with a favorable prognosis in adult patients with GBM treated with TMZ. We determined the incidence of pseudoprogression according to the MGMT methylation status and the potential value of DSC perfusion MR images for predicting pseudoprogression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
131
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(134 citation statements)
references
References 26 publications
1
131
1
1
Order By: Relevance
“…This result is not surprising given evidence that CBV or CBF measures or both have been seen in other recent (largely retrospective) studies to correlate with tumor grade and, in high-grade glial tumors, with cellular proliferation, response to treatment, and time to progression. 12,13,26,27,29,30,32,[39][40][41][42] In the current study, not only was the experts' confidence significantly affected by the addition of the perfusion imaging, but the management plan was actually changed in 5 of the 59 patient episodes of care (8.5%). Although this was not a diagnosticaccuracy study, we subsequently retrospectively reviewed these patients' medical records and found that the changes suggested by the perfusion imaging interpretations seemed to have aligned with the subsequent behavior of their tumors in 4 patients (1 patient's subsequent tumor behavior could not be determined).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This result is not surprising given evidence that CBV or CBF measures or both have been seen in other recent (largely retrospective) studies to correlate with tumor grade and, in high-grade glial tumors, with cellular proliferation, response to treatment, and time to progression. 12,13,26,27,29,30,32,[39][40][41][42] In the current study, not only was the experts' confidence significantly affected by the addition of the perfusion imaging, but the management plan was actually changed in 5 of the 59 patient episodes of care (8.5%). Although this was not a diagnosticaccuracy study, we subsequently retrospectively reviewed these patients' medical records and found that the changes suggested by the perfusion imaging interpretations seemed to have aligned with the subsequent behavior of their tumors in 4 patients (1 patient's subsequent tumor behavior could not be determined).…”
Section: Discussionmentioning
confidence: 86%
“…Studies have suggested that perfusion MR imaging performs reasonably well as a diagnostic test in the setting of treated patients, in that high-grade gliomas typically have relatively increased CBF and CBV and treatment-related effects are associated with a relative decrease in CBF and CBV. 11,16,[31][32][33]39 However, to our knowledge, there is a paucity of literature regarding the extent to which these perfusion MR imaging techniques might actually affect treatment decisions in a clinical setting-that is, whether they have diagnostic or therapeutic impact. In particular, it has been unclear whether a group of experienced physicians who specialize in the treatment of patients with brain tumor on a daily basis would actually use perfusion imaging or find it helpful in clinical decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…The group of patients with an unmethylated MGMT promoter showed a significant difference in mean rCBV between pseudoprogression and real progression, though the group with a methylated MGMT promoter showed no significant difference in another study. 49 These results suggest that predicting MGMT promoter methylation status from MR imaging may be challenging. .…”
Section: Discussionmentioning
confidence: 94%
“…Previous DSC-MR studies showed that true progression had significantly higher relative BV (rBV) than pseudoprogression [34,35] and TIN [36,37]. Using PCT, true progression showed significantly higher values of rBF, rBV, and PS than TIN [38][39][40].…”
Section: Differentiation Of True Progression From Post-treatment Effectsmentioning
confidence: 99%